Front Cover: Photonic Jet Writing of Quantum Dots Self‐Aligned to Dielectric Microspheres (Adv. Quantum Technol. 9/2021). Issue 9 (14th September 2021) - Ristori, Andrea; Hamilton, Travis; Toliopoulos, Dimosthenis; Felici, Marco; Pettinari, Giorgio; Sanguinetti, Stefano; Gurioli, Massimo; Mohseni, Hooman; Biccari, Francesco
Abstract : Quantum dots (QDs) are promising candidates for the large‐scale implementation of quantum information technologies. In article number 2100045, Andrea Ristori, Francesco Biccari and co‐workers present a novel laser writing technique based on the properties of dielectric microspheres and on the effects of hydrogen in dilute nitrides. This technique enables the fabrication of GaAs1− x N x QDs self‐aligned to the microspheres, leading to a 7‐fold enhancement of their luminescence collection with a NA = 0.7 objective. This simple approach can lead to new QD‐based devices.